Pellino-3 promotes endotoxin tolerance and acts as a negative regulator of TLR2 and TLR4 signaling. Issue 6 (26th August 2015) - Murphy, Michael B; Xiong, Yanbao; Pattabiraman, Goutham; Manavalan, Tissa T; Qiu, Fu; Medvedev, Andrei E
Abstract : Induction of endotoxin tolerance increases expression of Pellino-3, which acts as an inhibitor of TLR-driven MyD88- and TRIF-dependent pathways, while Pellino-3 ablation attenuates TLR4 tolerization. Abstract: Development of endotoxin tolerance in macrophages during sepsis reprograms Toll-like receptor 4 signaling to inhibit proinflammatory cytokines without suppressing anti-inflammatory and antimicrobial mediators and protects the host from excessive inflammation and tissue damage. However, endotoxin tolerance renders septic patients immunocompromised and unable to control secondary infections. Although previous studies have revealed the importance of several negative regulators of Toll-like receptor signaling in endotoxin tolerance, the role of Pellino proteins has not been addressed. The present report shows that the induction of endotoxin tolerance in vivo in mice and in vitro in human monocytes and THP-1 and MonoMac-6 macrophages increases the expression of Pellino-3. Overexpression of Pellino-3 in human embryonic kidney 293/Toll-like receptor 2 or 293/Toll-like receptor 4/myeloid differentiation factor-2 cells inhibited Toll-like receptor 2/4-mediated activation of nuclear factor-κB and induction of CXCL-8 mRNA, and Pellino-3 ablation increased these responses. Pellino-3-deficient THP-1 cells had elevated Toll-like receptor 2/4-driven tumor necrosis factor-α, interleukin-6 mRNA, and Toll-like receptor 4-driven CCL5 gene expression in response to Toll-like receptor agonists and heat-killed Escherichia coli and Staphylococcus aureus, cytokines controlled by the MyD88 and Toll-interleukin-1R domain-containing protein inducing interferon-β-mediated pathways, respectively. In addition, deficiency in Pellino-3 slightly increased phagocytosis of heat-killed bacteria. Transfected Pellino-3 inhibited nuclear factor-κB activation driven by overexpression of MyD88, TIR domain-containing adapter inducing interferon-β, interleukin-1R-associated kinase-1, and tumor necrosis factor receptor activator of nuclear factor-κB-binding kinase-1, TGF-β-activated kinase 1, and tumor necrosis factor receptor-associated factor-6, and inhibited interleukin-1R-associated kinase 1 modifications and tumor necrosis factor receptor activator of nuclear factor-κB-binding kinase 1 phosphorylation. Finally, Pellino-3 ablation in THP-1 decreased the extent of endotoxin tolerization. Thus, Pellino-3 is involved in endotoxin tolerance and functions as a negative regulator of Toll-like receptor 2/4 signaling.